Feasibility of an At-Home Experimental Circadian Misalignment Induction for Adolescents - Dean W. Beebe; Andrea L. Fidler; Laura McLaughlin; Sabrina Grove; Stephanie J. Crowley (Clocks & Sleep)
Despite extensive research on the effects of sleep restriction on adolescent health, the field lacks experimental methods to study the health effects of mistimed sleep, which is also common among adolescents. This paper describes a novel 3-week experimental protocol that was designed to compare sleep restriction, like what many adolescents experience on school nights, against sleep that meets the recommended duration but is timed to be relatively aligned or misaligned with their circadian phase. Healthy 14–18-year-olds, classified as early (“Lark”) and late (“Owl”) chronotypes, entered a six-night chronotype-aligned stabilization condition, followed by five nights of sleep restriction, a return to the stabilization schedule, and five nights of healthy sleep duration (HS). During HS, participants were randomly assigned to early-to-bed versus late-to-rise arms, intended to align with or misalign with their circadian phase. Actigraphy monitored sleep, and weekly dim-light melatonin onset (DLMO) assessed circadian phase. Analyses confirmed that the protocol met five key validation metrics related to differential attrition, sleep timing, circadian phase, and experimental induction of HS that is timed to be relatively aligned vs. misaligned with circadian phase. This protocol appears useful for future research into how misaligned sleep patterns, which occur regularly for many adolescents, may impact health.